2017
DOI: 10.1111/tid.12752
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial cell carcinoma after BK polyomavirus infection in kidney transplant recipients: A cohort study of veterans

Abstract: In this cohort of KTR veterans, no overall increased or decreased relative risk for malignancy was associated with evidence of prior BKPyV infection. A >8-fold increased risk of developing UCC after BKPyV infection was seen, although this risk was not found to be statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…KT recipients are at an increased risk for urothelial carcinoma. [4][5][6][7][8] Infection with oncogenic viruses could be a plausible explanation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KT recipients are at an increased risk for urothelial carcinoma. [4][5][6][7][8] Infection with oncogenic viruses could be a plausible explanation.…”
Section: Introductionmentioning
confidence: 99%
“…3KT recipients are at an increased risk for urothelial carcinoma. [4][5][6][7][8] Infection with oncogenic viruses could be a plausible explanation.Based on experimental models, JCV inoculation in cells that do not support viral replication leads to cancer formation. 9 Thus, human polyomaviruses have recently been categorized as "possible carcinogens" by the International Agency for Research in Cancer, 10 although a role for JCV in human cancers is not yet proved.…”
mentioning
confidence: 99%
“…Additional risk factors in the recipient could include the effects of immunosuppression 38 as well as a consequence of BK viral infection. 39 The first patient underwent an ABO incompatible living unrelated transplant, with desensitisation protocol (mainly plasmapheresis), in the early stage. The second recipient had a triple regimen immunosuppression, following an early acute rejection episode and she developed also BKV infection, another important risk factor for UC.…”
Section: Discussionmentioning
confidence: 99%
“…Adequately sensitive and specific diagnostics is vital in the assessment of cancer development in infected persons. This became evident to Rogers et al [17] when they examined 646 patients to estimate the relative risk of urinary tract cancer development related to BKPyV infection in patients with kidney transplantation between the year 2000 and 2009. The research results actually confirmed the 8-fold growth of UCC cancer development related to infection, but they were not statistically significant.…”
Section: Bkpyv In Kidney and Urinary Tract Cancermentioning
confidence: 99%